2023
DOI: 10.21037/tcr-22-2500
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a prognostic model and screening of potential natural compounds for acute myeloid leukemia

Abstract: Background Acute myeloid leukemia (AML) is one of the most common hematologic malignancies with a poor prognosis and high recurrence rate. The discovery of new predictive models and therapeutic agents plays a crucial role. Methods The differentially expressed gene that was explicitly highly expressed in The Cancer Genome Atlas (TCGA) and GSE9476 transcriptome databases were screened and included in the least absolute shrinkage and selection operator (LASSO) regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…In a recent issue, Sun et al ( 5 ) reported five hub genes ( RHOBTB2, PLA2G4A, IL2RA, CSRP1, and OLFML2A ) with prognostic relevance using two independent AML cohorts. Furthermore, the authors used chemoinformatics tools to propose natural compounds as potential ligands for proteins resulting from these genes to modulate the biological activity of these potential new targets ( 5 ). Two points deserve to be highlighted, the identification of new targets and the use of natural compounds in AML from data mining and chemoinformatics.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent issue, Sun et al ( 5 ) reported five hub genes ( RHOBTB2, PLA2G4A, IL2RA, CSRP1, and OLFML2A ) with prognostic relevance using two independent AML cohorts. Furthermore, the authors used chemoinformatics tools to propose natural compounds as potential ligands for proteins resulting from these genes to modulate the biological activity of these potential new targets ( 5 ). Two points deserve to be highlighted, the identification of new targets and the use of natural compounds in AML from data mining and chemoinformatics.…”
mentioning
confidence: 99%
“…On the other hand, the role of CSRP1 is still little known in AML, but its role as a potential oncogene was recently described in solid tumors ( 18 ). Given this background, the study conducted by Sun et al ( 5 ) proposes a new biomarker and consolidates some prognostic markers in AML, promoting progress in the field of study.…”
mentioning
confidence: 99%
See 2 more Smart Citations